Strategic bilingualism and symbolic prestige: English in Starbucks Indonesia’s Instagram marketing - Fuad Hasyim (Tefla Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2026)
This study examines how Starbucks Indonesia deploys English in its Instagram marketing, revealing mechanisms by which global brands sustain prestige hierarchies in multilingual digital spaces. Using mixed quantitative–qualitative discourse analysis of 60 purposively sampled posts (January 2024–December 2025), coded across Linguistic Landscape Theory, Foreign Consumer Culture Positioning, Digital Acculturation, and Symbolic Capital, the analysis identifies a hierarchical bilingual system rather than balanced code-switching. Findings show English dominates visual positions (76.7%), captions (75%), and transactional communication (56.7% CTAs), while “Indoglish” remains rare (1.7%). An inventory of 40 untranslated English terms serves as symbolic capital, with strategic exclusions (e.g., Venti) strengthening the maintenance of prestige. English density varies contextually, 86.7% in transactional content versus 51.1% in community campaigns, indicating acculturation as a tactical repertoire. The study contributes four theoretical advances: extending Linguistic Landscape Theory to digital platforms; providing empirical evidence of hierarchical language distribution; demonstrating acculturation as a context-dependent strategy; and integrating four theoretical domains into a unified model showing that prestige emerges through spatial positioning, repetition, exclusion, and contextual modulation, independent of comprehension. For global brands, the findings suggest hierarchical bilingualism is an effective strategy for balancing global prestige with local cultural competence.